2010 Canada Olympic & Paralympic Preparation - Henwood, D.; Pattenden, W. (5. International Forum on Elite Sport. Beijing, China, 3-6 September 2007, 2007)
2010 Canada Presentation Outline • Role of CSCs • Own The Podium • 2006-2007 Results • Paralympic Preparation • Olympic Preparation • Facilities Update